Endodontic anatomy of lower premolars in a subpopulation from the Mureş county. - Dakó Timea; Vlad Ramona-Elena; Stoica Alexandra-Mihaela; Kovăcs-Ivăcson; Monea Monica ("George Emil Palade" University of Medicine, Pharmacy, Science, and Technology of Targu Mures, 2021)
Background/Aim: Thorough knowledge of the endodontic anatomy and comprehensive understanding of root canal morphological variations are mandatory to ensure the successful outcome of the endodontic treatment. The purpose of this study was to compare the number of root canals of first and second lower premolars in a selected population to the root canal pattern reported by endodontic literature and to analyze the gender distribution.